2016
DOI: 10.4238/gmr.15027408
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical implications of enhancer of Zeste homolog 2 and p53 protein in squamous cell carcinoma and precancerous lesions in the cervix

Abstract: ABSTRACT. We investigated the expression and clinical implications of enhancer of Zeste homolog 2 (EZH2) and p53 protein in cervical squamous cell carcinoma (SCC) and precancerous lesions. EZH2 and p53 expressions in SCC (168), cervical intraepithelial neoplasia (CIN)-I (19), , and normal tissues (30) were detected by streptavidin-peroxidase-conjugation. The correlation between coexpression of EZH2 and p53 protein and the clinic pathological features and prognosis of SCC were discussed. The positive expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
4
0
0
Order By: Relevance
“…However, no significant correlation (p = 0.118) was obtained between tumor size and EZH2 immunoexpression (Table 2). This finding was similar to studies by Zhang et al, Jin et al, and Azizmohammadi et al who also documented insignificant association with p values of 0.849, 0.077, and 0.63 respectively [20,22,24].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, no significant correlation (p = 0.118) was obtained between tumor size and EZH2 immunoexpression (Table 2). This finding was similar to studies by Zhang et al, Jin et al, and Azizmohammadi et al who also documented insignificant association with p values of 0.849, 0.077, and 0.63 respectively [20,22,24].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, out of 60 cases of carcinoma cervix, high expression of EZH2 was present in 41 cases (68.3%) (Table 1). Similar to our study, Zhang et al investigated EZH2 expression in 168 cases of cervical SCC and found positive expression rate of 75.6% which was also statistically significant (p < 0.05) [20]. Liu et al also documented positive expression in 68.3% cases of cervical cancer [21].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations